Enhanced oscillation lifetime of a Bose–Einstein condensate in the 3D/1D crossover. (24th September 2015) - Yuen, B; Barr, I J M; Cotter, J P; Butler, E; Hinds, E A
Abstract: We have measured the damped motion of a trapped Bose–Einstein condensate, oscillating with respect to a thermal cloud. The cigar-shaped trapping potential provides enough transverse confinement that the dynamics of the system are intermediate between three-dimensional and one-dimensional. We find that the scaling of the damping rate with temperature is consistent with Landau theory, but that the damping rate for axial oscillations at a given temperature is consistently smaller than expected for a three-dimensional gas. We attribute this to the suppressed density of states for low-energy transverse excitations (essential excitations for axial Landau damping), which results from the quantization of the radial motion.